Remediation of chromium- and fluoride-contaminated groundwater by immobilized Citrobacter sp. on a nano-ZrO2 hybrid material. - Xilin Li (Public Library of Science (PLoS), 2021)
To effectively address excessive SO42-, Cr(VI), total chromium and F- in the groundwater of acidic mining areas, a facultative anaerobic bacterium, Citrobacter, with sulfate-reducing properties, tolerance to hexavalent chromium and the ability to reduce Cr(VI) to Cr(III) was isolated and domesticated. Based on microbial immobilization technology, a nano-ZrO2 polyacrylamide hybrid material was prepared as an embedding agent to form nano-ZrO2 polyacrylamide Citrobacter (ZPC) particles. ZPC was microscopically characterized, and the removal performance and mechanism of ZPC for SO42-, Cr(VI), total chromium and F- in groundwater were analyzed. The results of single-factor tests showed that the optimal reaction conditions included a reaction temperature of 35°C, Citrobacter dosage of 35% (volume ratio) in the particles and hybrid material dosage of 300 mL; under these conditions, the removal rates of SO42-, Cr(VI), total chromium and F- were 70.5%, 100%, 100% and 93.3%, respectively, and the pH value increased from 4.6 to 8.07. On this basis, the effects of the reaction layer type, influent hydraulic load and influent concentration on the removal efficiency of polluted groundwater were studied through dynamic experiments. The experimental results showed that ZPC particles were better than Citrobacter as a reaction layer; the optimal influent hydraulic load was 3.0 m3/(m2·d); the selectivity of ZPC particles to anions and anionic groups was different; and the order of adsorption selectivity was F- > Cr(VI) > SO42-.